2017 IEEE World Haptics Conference (WHC) 2017
DOI: 10.1109/whc.2017.7989956
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of the postural set during voluntary intermittent light finger contact as a function of hand dominance

Abstract: Abstract-Light fingertip contact with an earth-fixed referent decreases body sway. In a previous study Johannsen et al. (2014) demonstrated longer return-to-baseline of body sway for intermittent contacts of more than 2 seconds duration. This indicates that sway reduction with light tactile contact involves postural control strategies independent of the availability of tactile feedback and may depend on the intention to control body sway with light touch feedback. In the present study, we investigated the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Dolgilevica and colleagues [31] proposed a conceptual framework which emphasizes the role of body representations such as the postural configuration of the body as well as the size and shape of body segments in the spatial localization of touch. In a previous study, we observed effector-specific differences between participants' dominant and non-dominant hand in terms of sway after-effects following sudden removal of a Light Touch reference [32]. The after-effect, that is the time to return to no touch baseline sway, was prolonged when the dominant hand was used to keep the Light Touch contact.…”
Section: Plos Onementioning
confidence: 91%
See 1 more Smart Citation
“…Dolgilevica and colleagues [31] proposed a conceptual framework which emphasizes the role of body representations such as the postural configuration of the body as well as the size and shape of body segments in the spatial localization of touch. In a previous study, we observed effector-specific differences between participants' dominant and non-dominant hand in terms of sway after-effects following sudden removal of a Light Touch reference [32]. The after-effect, that is the time to return to no touch baseline sway, was prolonged when the dominant hand was used to keep the Light Touch contact.…”
Section: Plos Onementioning
confidence: 91%
“…The after-effect, that is the time to return to no touch baseline sway, was prolonged when the dominant hand was used to keep the Light Touch contact. As our participants were all right-handed, the observation implies that involvement of the left-hemisphere delayed switching between sets by keeping the Light Touch central postural set active for longer [32]. Thus, the control of body sway with Light Touch but without visual feedback may rely more on representations of somatotopy in the secondary somatosensory cortex [33] than representations of external space in the posterior parietal cortex.…”
Section: Plos Onementioning
confidence: 99%